The spanning plate as an internal fixator in complex distal radius fractures – a prospective cohort study. (28th May 2021) - Liechti, R; Babst, R; Hug, U; Link, B -C; van de Wall, B; Knobe, M; Beeres, F
Abstract: Objective: Minimal invasive temporary spanning plate (SP) fixation of the wrist has been described as an alternative treatment method in complex distal radius fractures (DRFs). The purpose of this study is to conduct an outcome analysis of all consecutive DRFs treated by SP fixation representing the so far largest published patient cohort outside the United States. Methods: Indication for SP fixation included DRFs with severe metaphyseal comminution, radiocarpal luxation fractures with concomitant ligamentous injuries and very distal intra-articular fractures lacking the possibility of adequate plate anchoring. All consecutive patients undergoing SP fixation of DRFs were prospectively included in a single level I trauma centre between 01/01/2018 and 31/12/2020. Post-operative assessments included radiological, functional and patient-rated outcomes at a minimum of 12 months follow-up. Results: In the mentioned timeframe, a total of 508 DRFs were treated operatively of which 28 underwent SP fixation. Average age was 58.1 years (range 22-95 years). The fracture type ranged from AO/OTA type B1.1 to C3.3 and included 8 fracture dislocations. SP removal was performed on average 3.7 months after the initial operation (range 1.4-6.5 months). The mean follow-up time was 14.5 months (range 12-24 months). Radiological evidence of fracture healing appeared on average 9.9 weeks (range 5-28 weeks) after the initial operation. One patient experienced oligosymptomatic non-union. Complications included 2 patients with tendon rupture and one patient with extensor tendon adhesions needing tenolysis at the time of plate removal leaving an overall complication rate of 12%. There was no implant failure and no infection. Mean satisfaction score was 8 (range 0-10) and mean visual analogue scale for resting pain was 0.9 (range 0-9). The mean PRWE score was 17.9 (range 0-59.5) and the mean DASH score was 16.6 (range 0-60.8). Grip strength averaged 23kg (range 4-74kg) amounting to 68% of the opposite side. Mean radial inclination, volar tilt and ulnar variance at 1 year were all within the acceptable limit predictive of symptomatic malunion. Conclusion: The radiological, functional and patient-rated outcomes in this study are remarkably good considering the complexity of the included fractures. Therefore, this method represents a valuable alternative for the treatment of complex DRFs in selected patients.